2015
DOI: 10.1002/elps.201300057
|View full text |Cite
|
Sign up to set email alerts
|

Study of the enantioseparation capability of chiral dual system based on chondroitin sulfate C in CE

Abstract: It has been reported that chiral dual system is able to improve the enantioseparation of enantiomers in many cases. Currently, the dual systems involved in CE chiral separation are mostly dual CDs systems, and the polysaccharides-based chiral dual system was reported in only one paper. To the best of our knowledge, the use of chondroitin sulfate C (CSC)-based dual system for enantiomeric separation has not been reported previously. Herein, four CSC-based chiral dual systems, namely CSC/glycogen, CSC/chondroiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, the chiral ionic liquid, which, in most cases, improves both efficiency and resolution significantly, is simple and cheap to synthesize . In addition, the analysis times of NEF , FXD , WAR , and COU were sufficiently lower than the ones reported in the literature.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, the chiral ionic liquid, which, in most cases, improves both efficiency and resolution significantly, is simple and cheap to synthesize . In addition, the analysis times of NEF , FXD , WAR , and COU were sufficiently lower than the ones reported in the literature.…”
Section: Discussionmentioning
confidence: 81%
“…The combination of these two CSs resulted in greater resolution values (>1.5), while in the case of a single‐CS system, no or partial chiral separations were achieved. In 2015, the polysaccharide chondroitin sulfate C (CSC) was combined with several CSs (chondroitin sulfate A, glycogen, HP‐β‐CD, and β‐CD), and the enantioseparation of different analytes was investigated . The results indicated that, in comparison to the single system, the system CSC/glycogen enhanced the enantioseparations significantly.…”
Section: Chiral Selectorsmentioning
confidence: 99%
“…Considering these differences between pairs of enantiomers, the development of enantioselective analytical methods is an important task. Several analytical techniques have been applied for the enantiomeric separation of antifungal compounds, such as gas chromatography (GC) [4], capillary electrophoresis (CE) [5][6][7][8][9][10][11], high-performance liquid chromatography (HPLC) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and supercritical fluid chromatography (SFC) [14,[32][33][34][35][36][37][38][39]. Commercially or hand-made chiral stationary phases (CSPs), based on different cellulose [12,[14][15][16][19][20][21][22][23][25]…”
Section: Introductionmentioning
confidence: 99%